Minimal residual disease detection by next-generation sequencing in multiple myeloma: Promise and challenges for response-adapted therapy - Ferla, Valeria; Antonini, Elena; Perini, Tommaso; Farina, Francesca; Masottini, Serena; Malato, Simona; Marktel, Sarah; Lupo Stanghellini, Maria Teresa; Tresoldi, Cristina; Ciceri, Fabio; Marcatti, Magda (Frontiers in Oncology, 2022)
Assessment of minimal residual disease (MRD) is becoming a standard diagnostic tool for curable hematological malignancies such as chronic and acute myeloid leukemia. Multiple myeloma (MM) remains an incurable disease, as a major portion of patients even in complete response eventually relapse, suggesting that a residual disease remains. Over the past decade, treatment landscape of MM has radically changed with the introduction of new effective drugs and the availability of immunotherapy, including targeted antibodies and adoptive cell therapy. Therefore, conventional serological and morphological techniques have become suboptimal for evaluation of depth of response. Recently, the IMWG introduced the definition of MRD negativity as the absence of clonal PC with a minimum sensitivity of <10−5 either by next-generation sequencing (NGS) using the LymphoSIGHT platform (Sequenta/Adaptative) or by next-generation flow cytometry using EuroFlow approaches as the reference methods. While definition of LymphoSIGHT platform (Sequenta/Adaptive) as the standard method derives from its large use and validation in clinical studies on the prognostic value of NGS-based MRD, other commercially available options exist. Recently, the LymphoTrack assay has been evaluated in MM demonstrating minimum sensitivity level of 10−5, hence qualifiying as an alternative effective tool for MRD monitoring in MM. Here we will review state-of-the-art methods for MRD assessment by NGS. We will summarize how MRD testing supports clinical trials as a useful tool in dynamic risk-adapted therapy. Finally, we will also discuss future promise and challenges of NGS-based MRD determination for clinical decision making. In addition, we will present our real-life, single-center experience with the commercially availble NGS strategy LymphoTrack-MiSeq. Even with the limitation of a limited number of patients, our results confirm LymphoTrack-MiSeq platform as a cost-effective, readily available and standardized workflow with a sensitivity of 10−5. Our real-life data also confirm that achieving MRD negativity is an important prognostic factor in MM.